2023
DOI: 10.3389/fpsyg.2022.1015921
|View full text |Cite
|
Sign up to set email alerts
|

Social exchange theory: Systematic review and future directions

Abstract: Social exchange theory (SET) is one of the most influential theories in social sciences, which has implications across various fields. Despite its usefulness being a typical social transaction, there is a need to look at it from the lens of psychological transactions to further its evolution and to identify future directions. After generally reviewing 3,649 articles from the Social Science Citation Index and Scopus, a total of 46 articles were selected for final review using a comprehensive systematic review a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(74 citation statements)
references
References 77 publications
0
29
0
Order By: Relevance
“…The results of this study showed that nurses' ratings of ethical leadership were positively correlated with nurses' well-being and workplace mindfulness in central China (r = .507, .376, p < .01), and the higher the ratings of ethical leadership, the better the nurses' well-being experience. Based on social exchange theory, it is known that when one party of the exchange benefits the behaviour of the other party, the other party tends to give more positive feedback (Ahmad et al, 2022).…”
Section: Correlation Of Ethical Leadership Workplace Mindfulness and ...mentioning
confidence: 99%
See 2 more Smart Citations
“…The results of this study showed that nurses' ratings of ethical leadership were positively correlated with nurses' well-being and workplace mindfulness in central China (r = .507, .376, p < .01), and the higher the ratings of ethical leadership, the better the nurses' well-being experience. Based on social exchange theory, it is known that when one party of the exchange benefits the behaviour of the other party, the other party tends to give more positive feedback (Ahmad et al, 2022).…”
Section: Correlation Of Ethical Leadership Workplace Mindfulness and ...mentioning
confidence: 99%
“…The results of this study showed that nurses' ratings of ethical leadership were positively correlated with nurses' well‐being and workplace mindfulness in central China ( r = .507, .376, p < .01), and the higher the ratings of ethical leadership, the better the nurses' well‐being experience. Based on social exchange theory, it is known that when one party of the exchange benefits the behaviour of the other party, the other party tends to give more positive feedback (Ahmad et al, 2022). In the clinical work environment, because ethical leaders have the qualities of fairness, impartiality and honesty, they can provide clinical nurses with reasonable career development opportunities and give them affirmation, help and emotional support in their work to avoid unfair treatment, so they effectively improve nurses' sense of belonging and identity to the department, thus further improving their work enthusiasm and psychological experience (Houston et al, 2022).…”
Section: Dicussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We propose an alternative model that combines elements from Social Exchange Theory (Ahmad et al, 2023) and Commitment-Trust Theory (Morgan & Hunt, 1994). The Social Exchange Theory provides insights into the exchange of value between companies and consumers, focusing on perceived benefits, customer satisfaction and loyalty (Ahmad et al, 2023).…”
Section: A Rival Alternative Framework: the Three-stage Modelmentioning
confidence: 99%
“…What makes a life meaningful is not simply a process of interaction but also participating in a cultural system that contains norms, values, and shared information. Social relationships and meanings are positively linked with each other (Baumeister, 2018;Ahmad et al, 2022). Islam (2004) proposes that in a collectivistic culture, people give priority to their families and perform activities on their behalf.…”
Section: Moderating Role Of Collectivismmentioning
confidence: 99%